ANALISIS KETERLIBATAN PELAJAR DALAM DEMONSTRASI DARI SISI ASAS HUKUM DAN HAK ASASI MANUSIA - Sarip, Sarip (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Embedded gray and white writing for High School students or equivalent, it is categorized as a beginner voter in Indonesia. In September 2019 there was a ban on demonstrations involving white and gray voices. The aim and study focuses on the discussion of white and gray voices in demonstrations seen from the substance of electoral law seen from the principle of lex specialis derogat legi generali. Its usefulness, it gives enlightenment to the minimum age limit to vote and can be legally accounted for and election justice. The arguments of politicians, bureaucracy, and education in the assessment of white and gray are still children and unstable. The gray-white voice opposes ordinary use to crank up the voice and anticipate abstentions. The substance of democratic elections, white and gray votes have the same rights and obligations, unstable age is politicized substance to prevent abstentions, making it a stepdaughter of democracy. Countries that want elections that are more mature than they exist revitalize elections on demonstrations.